THE SPECIFICITY OF SOCIAL CONFLICTS AND WAYS OF THEIR PERMISSION - Z. Adzhieva (Вестник университета)
Annotaion. The article considers the specificity of social conflicts. The causes of their occurrence in modern society; positive and negative functions of social conflict. The author considers quantitative and qualitative indicators of social tension; main stages in the development of social contradictions and ways of resolving social conflicts.